2019
DOI: 10.1177/1558925019840874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air gap, fibre type and blend ratio on sound absorption performance of needle-punched non-woven fabrics

Abstract: This article reports a study on the effect of different natural fibres, their blend ratios and varying air gaps between a needle-punched non-woven fabric and polystyrene backing on the sound absorption coefficients of the needle-punched non-woven fabrics. These parameters as well as their interactive effects were studied by variance analysis. The air gap varied from 0 to 25 mm in 5 mm increments; three natural fibre types (agave, flax and waste wool) were used; each one blended with polyester fibres in three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similar results are obtained by increasing the material's thickness, which can improve the sound absorption coefficients at low, middle, and high frequencies due to an increase in sound energy losses. As observed in other studies [28], for achieving higher sound absorption coefficients at low frequencies by using a thicker material, it can simply be altered by incorporating an air gap, thereby reducing the number of fibers required. Consequently, this investigation has once again proved that if the material's thickness increases with an increase in airgap, the sound absorption coefficient increases.…”
Section: Effect Of Air Gap and Perforation Ratio On Sound Absorption ...mentioning
confidence: 99%
“…Similar results are obtained by increasing the material's thickness, which can improve the sound absorption coefficients at low, middle, and high frequencies due to an increase in sound energy losses. As observed in other studies [28], for achieving higher sound absorption coefficients at low frequencies by using a thicker material, it can simply be altered by incorporating an air gap, thereby reducing the number of fibers required. Consequently, this investigation has once again proved that if the material's thickness increases with an increase in airgap, the sound absorption coefficient increases.…”
Section: Effect Of Air Gap and Perforation Ratio On Sound Absorption ...mentioning
confidence: 99%
“…Porous sound-absorbing materials are one of the most widely used sound-absorbing materials, which have good sound-absorbing performance in the highfrequency band, including fibers, [99][100][101][102] foam, [103][104][105][106] and particle [107][108][109][110] sound-absorbing materials. Within porous materials, there are a lot of tiny pores that link to the outside world and each other.…”
Section: Pvdf-based Porous Sound-absorbing Materialsmentioning
confidence: 99%
“…It is widely believed that the presence of air gap in the back of porous sound absorbers benefits their sound absorption performance. [42][43] Seddeq et al 44 found that the inserting of air gaps and its thickness showed evident effect on the sound absorption properties including absorption peak and absorption curves of the porous fibrous materials. Thus, air gaps with different thickness are set at the back of the sample to investigate their effect on the sound absorption properties.…”
mentioning
confidence: 99%